INDONESIAN DEMOCRACY PROMOTION: Between Normative and Strategic Commitments - Erawan, I Ketut (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Indonesia’s reasons to launch democracy promotion through the Bali Democracy Forum (BDF) in 2008, and its continued efforts in the future, are guided by three commitments: strategic commitments, normative commitments, and mixed commitments. Viewing democracy promotion as a foreign policy enables us to advance the understanding of the motives, reasons, and rationality of a country like Indonesia in supporting democracy. The existing debates on models, mechanisms, and effects of democracy promotion tend to ignore the salience of reasoning behind the initiatives of democracy promotion. Understanding the reasonings and motives of democracy promotion would help us to better understand why certain models and mechanisms are selected.gb777